A Qualitative Analysis of Middle and High School Teacher Perceptions of Schoolwide Positive Behavior Supports. (October 2016) - Feuerborn, Laura L.; Wallace, Caroline; Tyre, Ashli D.
Full stakeholder support for any innovation can be difficult to achieve, particularly in complex systems such as middle and high schools. Increasingly, obtaining middle and high school teacher support for Schoolwide Positive Behavior Supports (SWPBS) is identified as a challenging yet crucial element of implementation. The reasons behind these challenges are not well understood; thus, the purpose of this study was to attain a better understanding of the SWPBS-related needs and concerns of middle and high school teachers. Thematic analysis was used to analyze open-ended concerns statements and statements of need from teachers working in 19 middle and high schools. Regardless of SWPBS implementation level, the most prevalent concerns pertained to staff support and consensus, and the most prevalent needs were related to collaboration. There were high levels of consistency in concerns and needs, with a few differences found in the concerns and needs statements of teachers in implementing and low-implementing schools. Full results, limitations, and implications for future research and practice are discussed.